Multiple Cavitating Nodules in a Renal Transplant Recipient - Sharla-Rae J Olsen; Mohit Bhutani (Canadian Respiratory Journal)
Pulmonary nodules are common following solid organ transplantation and vary in etiology. Nodules with central cavitation are most likely to be of infectious origin in the post-transplant population. A novel presentation of post-transplant lymphoproliferative disorder manifesting as multiple cavitating pulmonary nodules is described. The patient, a 45-year-old female renal transplant recipient, presented with constitutional symptoms and a chest x-ray showing multiple bilateral cavitating lesions. A computed tomography scan confirmed innumerable, randomly dispersed, cavitating nodules in the lung parenchyma. Multiple large hypodense lesions were identified in the liver and spleen. The appearance of the native and transplanted kidneys was normal. A liver biopsy identified an Epstein-Barr virus-negative, diffuse, large B cell lymphoma. Repeat imaging after treatment with a cyclophosphamide, hydroxydaunorubicin, oncovin and prednisone/prednisolone regimen demonstrated dramatic resolution of all lesions. The present case represents a unique radiographic presentation of post-transplant lymphoproliferative disorder not previously reported in the literature.